Thermal and spectroscopic investigation on N,N-dimethylbenzylamine based cyclopalladated compounds containing isonicotinamide - Stevanato, Alessandra [UNESP]; Mauro, Antonio Eduardo [UNESP]; Netto, Adelino Vieira de Godoy [UNESP] (Springer, 2009)
Synthesis, spectroscopic characterization and thermal analysis of the [Pd(dmba)(Cl)(iso)] (1), [Pd(dmba)(NCO)(iso)] (2), [Pd(dmba)(N(3))(iso)] (3) and [Pd(dmba)(Br)(iso)] (4) (dmba = N,N'-dimethylbenzylamine; iso = isonicotinamide) compounds are described in this work. The complexes were investigated by infrared spectroscopy (IR), differential thermal analysis (DTA) and thermogravimetry (TG) and the residues of the thermal decomposition were identified as Pd(o) by X-ray powder diffraction. The thermal stability order of the complexes varied as [Pd(dmba)(Cl)(iso)] (1) > [Pd(dmba)(Br)(iso)] (4) > [Pd(dmba)(NCO)(iso)] (2) > [Pd(dmba)(N(3))(iso)] (3).
Keywords: Palladium(II); Isonicotinamide; Spectroscopy; Thermal behavior